Design and expression of peptides with antimicrobial activity against Salmonella typhimurium. (1st August 2016) - Porta, Amalia; Petrone, Anna Maria; Morello, Silvana; Granata, Ilaria; Rizzo, Francesca; Memoli, Domenico; Weisz, Alessandro; Maresca, Bruno
Summary: We showed previously that insertion of Synechocystis Δ 12 ‐desaturase in salmonella's membrane alters membrane physical state (MPS), followed by the expression of stress genes causing inability to survive within murine macrophages (MΦ). Recently, we showed that expression of one membrane lipid domain (MLD) of Δ 12 ‐desaturase (ORF200) interferes with salmonella MPS, causing loss of virulence in mice and immunoprotection. Here, we postulate that an α‐antimicrobial peptide (α‐AMP) intercalates within membrane lipids, and depending on its amino acid sequence, it does so within specific key sensors of MLD. In this study, we choose as target for a putative synthetic AMP, PhoP/PhoQ, a sensor that responds to low Mg 2+ concentration. We synthesised a modified DNA fragment coding for an amino acid sequence (NUF) similar to that fragment and expressed it in salmonella typhimurium. We showed that the pattern of gene expression controlled by PhoP/PhoQ highlights dysregulation of pathways involving phospholipids biosynthesis, stress proteins and genes coding for antigens. RNA‐Seq of strain expressing ORF200 showed that the pattern of those genes is also altered here. Accumulation of NUF conferred temporary immunoprotection. This represents a powerful procedure to address synthetic α‐AMPs to a specific MLD generating live non‐virulent bacterial strains.